2012
DOI: 10.1039/c2cc31955a
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity and π-bond covalency: prominent intermolecular covalent bonding interaction of a Kekulé hydrocarbon with very significant singlet biradical character

Abstract: An anthracene-linked bisphenalenyl Kekulé molecule with very significant singlet biradical character has shown a prominent covalent bonding interaction between molecules in a molecular aggregate. High aromatic stabilization energy in the anthracene linker is responsible for the significant singlet biradical character.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 15 publications
(2 reference statements)
4
78
1
Order By: Relevance
“…Tetraphenyl derivatives 12 and 13 of 10 and 11 were prepared by multistep syntheses. 35,36 X-ray analysis revealed that 12 and 13 form 1D stacks in a slipped stacking arrangement with a superimposed phenalenyl overlap, which was almost identical to that of 8 and 9 ( Figure 8). Very short ππ contacts (3.170 ¡ for 12, 3.122 ¡ for 13) were also observed.…”
Section: 32mentioning
confidence: 89%
“…Tetraphenyl derivatives 12 and 13 of 10 and 11 were prepared by multistep syntheses. 35,36 X-ray analysis revealed that 12 and 13 form 1D stacks in a slipped stacking arrangement with a superimposed phenalenyl overlap, which was almost identical to that of 8 and 9 ( Figure 8). Very short ππ contacts (3.170 ¡ for 12, 3.122 ¡ for 13) were also observed.…”
Section: 32mentioning
confidence: 89%
“…Intermolecular covalent bonding interactions were investigated with single crystals of tetraphenyl derivatives 19 and 20 . X‐ray analysis revealed that 19 and 20 afforded 1D chains in a slipped stacking arrangement with the superimposed phenalenyl moieties overlapping, which were almost identical to that of 13 (Figure ) . The very short π–π contacts (3.16 Å for 19 , 3.15 Å for 20 ) indicate the adequate covalent bonding interaction between molecules.…”
Section: Singlet Biradicals Based On Bisphenalenylmentioning
confidence: 89%
“…Intramolecular covalent bonding interactions of the two unpaired electrons in 15 and 16 were assessed with di‐ tert ‐butyl tetraphenyl derivatives 17 and 18 . The SQUID measurements of powdered 17 and 18 revealed smaller singlet–triplet energy gaps (16 kJ/mol for 17 , ∼8 kJ/mol for 18 ) than that of 10 .…”
Section: Singlet Biradicals Based On Bisphenalenylmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that Clar structure shown in Scheme 5b is reinforced by all applied aromaticity indices (see Table S1 in Supporting Information). Summarizing, in 2,3-quinones for n > 2, the diradical singlet situation is favored, as in the case of the acenes [25,59,61,63] and in other polycyclic aromatic hydrocarbons [26][27][28][29][30][64][65][66][67][68][69] and graphene nanoflakes [70,71]. Therefore, for 2,3-isomers, only the results of the ground states (singlet closed shell for n ≤ 2 and singlet open shell for n ≥ 3) are presented below.…”
Section: Resultsmentioning
confidence: 99%